2021
DOI: 10.1002/slct.202101934
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline‐Supported Tungsten‐Catalyzed Green and Selective Oxidation of Alcohols

Abstract: Polyaniline (PANI)-supported tungsten could be easily fabricated by immersing PANI into the tungsten salt solution. It was a high efficient catalyst for alcohol oxidation reaction to produce carbonyls. Notably, the selectivities of the oxidation of primary alcohols were good, affording aldehydes as the specific products. The high catalytic activity might attribute to the coordination of nitrogen in PANI with tungsten in the materials, while the unique structure afforded the catalyst high selectivity for primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…[9,10] The nucleophilic attack of the substrate hydroxyl to the positive center of manganese in the first step reaction is the key to control the reaction selectivity, and the produced carbonyls (especially for aldehydes) were difficult to be overoxidized for their poor nucleophilic reactivities ensuring the first step reaction on the catalytic Mn = O. [8] Because of the complex multicomponent catalyst and the variable free radical intermediates, the reaction might also occur via other routes, but the mechanism illustrated in Scheme 2 should be mostly like to occur according to the experimental results, the characterization of the materials as well as the reference reports. In conclusion, we have developed a novel mesoporous Mn-Se/Al 2 O 3 catalyst for the oxidation of alcohols affording carbonyls in 58%-83% yields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] The nucleophilic attack of the substrate hydroxyl to the positive center of manganese in the first step reaction is the key to control the reaction selectivity, and the produced carbonyls (especially for aldehydes) were difficult to be overoxidized for their poor nucleophilic reactivities ensuring the first step reaction on the catalytic Mn = O. [8] Because of the complex multicomponent catalyst and the variable free radical intermediates, the reaction might also occur via other routes, but the mechanism illustrated in Scheme 2 should be mostly like to occur according to the experimental results, the characterization of the materials as well as the reference reports. In conclusion, we have developed a novel mesoporous Mn-Se/Al 2 O 3 catalyst for the oxidation of alcohols affording carbonyls in 58%-83% yields.…”
Section: Resultsmentioning
confidence: 99%
“…A plausible mechanism of the reaction was proposed on the basis of the experimental results, the characterization of the materials, and the reference reports (Scheme 2). [8–10, 19, 32–35] Since ICP‐MS analysis showed that the content of selenium in the material was very few and control experiments in Scheme 1 demonstrated that manganese catalyst was even more active than selenium, in this reaction, manganese was considered to be the major catalytic element, [32] while selenium should be the cocatalyst that could promote the activity of manganese owing to its oxygen carrier features [9, 10, 33] as well as the catalyst morphology improvement during the materials fabrication process [19] (Figure 6b). As being attested by HRTEM, XPS, and XRD, high‐valent manganese in the material existed in the supported MnO 2 form (Figures 3d, 5, and 6a), and it dispersed evenly on Al 2 O 3 support affording sufficient contact with the organic reactants for the large specific surface area of the material (Figures 4 and 6b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Although, in previous studies, various catalytic systems and reagents have been introduced for improving the chemical conversion of alcohols to aldehydes, the development of new efficient oxidation systems based on a heterogeneous catalyst in terms of economic and environmental reasons would be very valuable. [10][11][12][13] Nowadays, ionic liquids (ILs) for their unique exceptional physicochemical properties including, non-flammability, negligible vapor pressure, chemical and thermal stabilities, wide liquid temperature, and outstanding solvating potential have been known as green alternatives for volatile organic solvents, and have triggered significant attentions in different scientific and industrial fields such as spectroscopy, electrochemistry, microextractions, and catalysts in organic synthesis. [14][15][16][17][18] Recently, the introduction of a new category of ILs family, namely dicationic ionic liquids that contain two cationic head group and linked with a rigid or flexible spacer and two anions has attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…The development of polyanilines (PANIs) as environmentally benign supports may afford the resolutions for catalyst development in industrial grade production. PANIs are low toxic. , and can be easily prepared via the oxidative polymerization of the abundant and cheap anilines. The nitrogen-containing groups on PANIs endow the material strong coordination with metals, and the PANIs-anchored metal catalysts (M@PANIs) have already been widely employed in a series of reactions, such as the oxidation reactions and the coupling reactions. Notably, in comparison with inorganic supports, PANIs are versatile, and the catalytic activities of the as-prepared M@PANIs can be adjusted by introducing functionally groups on aniline monomers, which are easily accessible and can be purchased at very low price . Recently, we found that the Zn@PANIs could catalyze the condensation of lactic acid to produce lactide with high chemical and optical purity in good yields.…”
Section: Introductionmentioning
confidence: 99%